The facebook effect: the inside story of the company that is connecting the world - Kirkpatrick, David (New York : Simon & Schuster Paperbacks, 2010)
Facebook (Firm).
Includes bibliographical references and index.
Keywords: Internet industry -- United States; Online social networks -- History